Geo-spatial knowledge and intelligence. 5th International Conference, GSKI 2017, Chiang Mai, Thailand, December 8-10, 2017, revised selected papers /: 5th International Conference, GSKI 2017, Chiang Mai, Thailand, December 8-10, 2017, revised selected papers. Part II : (2018) - Unknown
No abstract available